2023
DOI: 10.1071/wf22152
|View full text |Cite
|
Sign up to set email alerts
|

Slope effect on junction fire with two non-symmetric fire fronts

Abstract: Background. In Pedrógão Grande on 17 June 2017, two fire fronts merged and the propagation of the fire was influenced by the interaction of these non-symmetric fire fronts. Aims. This wildfire motivated us to study a junction fire with two non-symmetrical fire fronts. The analysis of the movement of the intersection point and the angle (γ) between the bisector of the fire lines and the maximum rate of spread (ROS) direction is of particular relevance. Methods. The study was carried out at Forest Fire Laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Slope was considered an important factor affecting surface fire behavior [54], and this study found that slope also affects sub-surface fire behavior. The sub-surface fire behavior in the vertical direction was greatly affected by slope at the initial stage, and the dividing point of peak temperature was 15 cm in the horizontal direction.…”
Section: Discussionmentioning
confidence: 87%
“…Slope was considered an important factor affecting surface fire behavior [54], and this study found that slope also affects sub-surface fire behavior. The sub-surface fire behavior in the vertical direction was greatly affected by slope at the initial stage, and the dividing point of peak temperature was 15 cm in the horizontal direction.…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence that after 1930 hours, both fires had their inner flanks very close to each other, making a small angle between them, therefore with the ideal conditions to merge as a junction fire, studied by Viegas et al (2012), Raposo et al (2018) and Ribeiro et al (2023). Between 1930 and 2030 hours, the process of merging induced very strong winds in the area ahead of the fire.…”
Section: Merging Of the Two Firesmentioning
confidence: 99%
“…In these equations, we use as reference ROS values the socalled basic ROS R o , (Viegas and Pita 2004;Raposo et al 2014Raposo et al , 2018Xie et al 2014;Rodrigues et al 2019;Viegas et al 2021Viegas et al , 2022Ribeiro et al 2022Ribeiro et al , 2023) that corresponds to a linear fire spreading in the same fuel under no-wind and no-slope conditions.…”
Section: Scaling Distance and Fire Spreadmentioning
confidence: 99%